ANALISA VARIASI KECEPATAN PUTARAN PISAU TERHADAP KINERJA MESIN PERAJANG DAN HASIL IRISAN KERIPIK - Dwiyanto, M Ikbar; Arnoldi, Dwi; Azharuddin (Politeknik Negeri Sriwijaya, Indonesia, 2024)
The development of today's technology encourages the innovation of Technological developments encourage innovation in slicing chips that are done manually, now developing using machines. The quality of the chips is determined by the taste, crispness, color and shape of the slices. This research aims to test and determine the best knife rotation speed on a chips chopper machine.The rotational speed of the knife is one of the determining factors for producing sliced chips that are in accordance with the wishes of consumers. This test will be carried out by adjusting the blade rotation speed using a dimmer, then slicing the chips according to the treatment. The treatment combination of blade rotation speed was 1303 rpm, 1355 rpm and 1375 rpm and the materials used were cassava, potatoes and bananas. Research data will be analyzed using quantitative methods. Based on research conducted that the highest effective capacity of the machine is at a blade rotation speed of 1375 rpm with cassava material of 26.74 kg/hour, the best yield of enumeration at a blade rotation speed of 1375 rpm with cassava material is 90%. The best percentage of intact slices was found at a blade rotation speed of 1303 rpm with potato material, namely 34%, half whole slices at a blade rotation speed of 1355 rpm with cassava material, namely 30%, and crushed slices at a knife rotation speed of 1375 with cassava material, namely 42%.